Efektifitas Metode Tartili dalam Meningkatkan Kemampuan Membaca Al-Qur’an Santri Siraajul Ummah Bekasi - Muri Noer Fitriah; Masykur H Mansyur; Neng Ulya (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2022)
The Tartili method is a method in which santri or students read the Qur'an directly (without spelling) and include/practice the discussion of Tartil reading according to the rules of Ulumul Tajwid and Ulumul Ghorib, and is one of the most practical methods and practices for studying Al-Tajwid. Qur'an faster to help students read the Qur'an. Qualitative approach is